Gender identity with the wrong name. - Gina Cabeza Monroy (Case Reports)
This is the case of a six-year-old schoolchild —identified as J— who was born with ambiguous external genitalia. Upon medical recommendation, the child was registered as male by the parents; however, further testing (diagnostic imaging and karyotyping) showed that the child was biologically female. Based on this, the parents started the judicial process to change their child’s name, and the judge ordered a forensic psychiatric evaluation to determine the child’s true sex1. When the forensic study concluded that the child’s sex was female, the result was transmitted to government authorities and the name was corrected in the child’s civil registry.